The diary of a young girl - Frank, Anne, 1929-1945; Frank, Otto, 1889-1980; Pressler, Mirjam (New York : Alfred A. Knopf, 2010)
An uncut edition of Anne Frank's diary includes entries originally omitted by her father and provides insight into Anne's relationship with her mother.
"First included in Everyman's Library, 2010."
"English translation copyright 1995 by Doubleday."
Keywords: Frank, Anne, -- 1929-1945 -- Diaries; Frank, Anne, -- 1929-1945 -- Diaries; Holocaust, Jewish (1939-1945) -- Netherlands -- Amsterdam -- Personal narratives; Jews -- Persecutions -- Netherlands -- Amsterdam; Jews -- Netherlands -- Amsterdam -- Diaries; Holocaust, 1939-1945 -- Personal narratives; Jews -- Persecutions -- Amsterdam (Netherlands); Jews -- Amsterdam (Netherlands) -- Diaries; Amsterdam (Netherlands) -- Ethnic relations; Amsterdam (Netherlands) -- Ethnic relations